A new species of Globicornis Latreille (Coleoptera: Dermestidae) from Baltic amber, with a key to fossil species - Bukejs, Andris; Háva, Jiří (Zootaxa, 2018)
Based on a well-preserved specimen from Eocene Baltic amber, the fourth fossil species belonging to the genus Globicornis Latreille (Coleoptera: Dermestidae: Megatominae), G. groehni sp. nov., is described and illustrated. A key to the species of Globicornis known from Baltic amber is also provided. The addition of this species further improves our knowledge about dermestids in Baltic amber, and moves us closer to the level of taxonomic coverage needed for detailed ecological studies based upon the coleopteran assemblage within the deposit.